Thorium–phosphorus triamidoamine complexes containing Th–P single- and multiple-bond interactions - Elizabeth P. Wildman; Gábor Balázs; Ashley J. Wooles; Manfred Scheer; Stephen T. Liddle (Nature Communications, 2016)
Abstract Despite the burgeoning field of uranium-ligand multiple bonds, analogous complexes involving other actinides remain scarce. For thorium, under ambient conditions only a few multiple bonds to carbon, nitrogen, oxygen, sulfur, selenium and tellurium are reported, and no multiple bonds to phosphorus are known, reflecting a general paucity of synthetic methodologies and also problems associated with stabilising these linkages at the large thorium ion. Here we report structurally authenticated examples of a parent thorium(IV)–phosphanide (Th–PH2), a terminal thorium(IV)–phosphinidene (Th=PH), a parent dithorium(IV)–phosphinidiide (Th–P(H)-Th) and a discrete actinide–phosphido complex under ambient conditions (Th=P=Th). Although thorium is traditionally considered to have dominant 6d-orbital contributions to its bonding, contrasting to majority 5f-orbital character for uranium, computational analyses suggests that the bonding of thorium can be more nuanced, in terms of 5f- versus 6d-orbital composition and also significant involvement of the 7s-orbital and how this affects the balance of 5f- versus 6d-orbital bonding character.